2021
DOI: 10.46690/ager.2021.02.05
|View full text |Cite
|
Sign up to set email alerts
|

Techniques used to calculate shale fractal dimensions involve uncertainties and imprecisions that require more careful consideration

Abstract: Wood, D. A. Techniques used to calculate shale fractal dimensions involve uncertainties and imprecisions that require more careful consideration. Advances in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 25 publications
(33 reference statements)
0
28
0
Order By: Relevance
“…Thus, the well development of mesopores is favorable for shale gas exploration. With the increase in pore size, the proportion of adsorbed gas decreases and the proportion of free gas increases, leading to the increased initial production of shale gas well [50][51][52].…”
Section: Ssa and Pv Characteristicsmentioning
confidence: 99%
“…Thus, the well development of mesopores is favorable for shale gas exploration. With the increase in pore size, the proportion of adsorbed gas decreases and the proportion of free gas increases, leading to the increased initial production of shale gas well [50][51][52].…”
Section: Ssa and Pv Characteristicsmentioning
confidence: 99%
“…Liu et al presented a comparative study of all the FHH, Neimark, and Wang–Li fractal models applied to a suite of Bakken shales form the Williston Basin (USA), noting discrepancies in the results of the methods related to the PSDs of certain samples. Wood highlighted the uncertainties involved in the fractal values derived by each of the FHH, Neimark, and Wang–Li fractal models and illustrated the benefits of an integrated interpretation involving all three methods. This study compares the FHH, Neimark, and Wang–Li fractal determination methods applied to suites of organic-rich shale samples from the two India Permian basins (North Karanpura and Raniganj).…”
Section: Introductionmentioning
confidence: 97%
“…Most studies published to date have applied, in isolation, the FHH fractal determination method to N 2 gas adsorption isotherm data. ,,,, Consequently, the two fractal dimensions ( D 1 and D 2 ) derived from the FHH method have been widely used to calculate the surface area and structures of the porous materials. However, several studies have reported potential underestimation of pore fractal dimensions from N 2 adsorption isotherms when applying the FHH method, leading to uncertainty in pore texture interpretations of certain porous media. , It remains ambiguous as to whether the limited reach of N 2 gas to the micropores, is a key factor influencing the fractal dimension calculations. Important questions need to be answered regarding the relative merits of the FHH, Neimark, and Wang–Li fractal determination methods applied to organic-rich shales and the relationship of their derived fractal dimensions to PSD and thermal maturity.…”
Section: Introductionmentioning
confidence: 99%
“…Fractal geometry is a powerful analytical tool for the characterization of complex materials. Fractal geometric parameters measured directly from pore scale images can also be volume-averaged, which thus reveal the influence of pore structure on macroscale parameters like permeability [24][25][26][27]. Fractal dimension is a scale-invariant parameter that characterizes the extent of complexity of pore space geometry [28].…”
Section: Introductionmentioning
confidence: 99%